The Da’wah Movement and Indonesia’s Moral Crisis: Between Mental Revolution and Akhlak Revolution - Dianto, Icol; Bin Don, Abdul Ghafar; Khusairi, Abdullah; Toni, Hariya (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2025)
This article aims to discuss the contestation of discourse in improving the nation's morality between two movements: the Mental Revolution—an initiative to reform the nation's character through modernization of mindset and work ethic, introduced by President Joko Widodo—and the Akhlak Revolution, a da'wah movement advocating the restoration of individual morality based on Islamic values, popularized by Habib Rizieq Shihab. The analysis in this article employs a political approach grounded in Michel Foucault's postmodern theoretical framework, which provides the basis for the discussion. The contestation between the two revolutions reflects ideological differences and power dynamics that shape the discourse on morality in society. Using a qualitative-interpretive research method, data were collected from YouTube using digital documentation techniques and analyzed through source triangulation validity testing, as proposed by Miles and Huberman. The findings reveal both conceptual and practical distinctions between the Mental Revolution and the Akhlak Revolution. The Mental Revolution is viewed as more pragmatic, grounded in state policies targeting civil servants and the bureaucracy, whereas the Akhlak Revolution emphasizes individual moral improvement through a religious framework. From a Foucauldian perspective, this distinction illustrates two forms of disciplinary power: the state exerts control through formal policy, while religious institutions influence morality through social norms and values. Although both initiatives offer responses to moral degradation, each has also faced criticism and resistance. This article argues for the need for synergy between state and religious approaches to promote more comprehensive moral transformation within society.